Wanita dan Pandemi Covid-19: Sebuah Beban Khas untuk Wanita - Vania P Hanjani (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
The Covid-19 pandemic is a burden for all groups with different impacts. In addition to a pandemic that has an impact on physical health, mental health is also a discussion that needs to be deepened again. Therefore, this study will discuss how the Covid-19 Pandemic will affect the role of individuals, especially the role of a woman in the family. Not only taking care of household needs, women must also manage their unstable household economy due to the Pandemic and must continue to carry out proper parenting for their children. Not only parenting, the education of children is also the responsibility of women as mothers because the center of activity is now in the house. Their burdens increased during the Covid-19 pandemic, especially after the government imposed the PSBB or Large-Scale Social Restrictions and Work From Home, which made some individuals have limited space to move. Using Lazarus, Folkman and Selye's stress and coping theory, this study reveals the stressors faced by women in the midst of the pandemic.